INTEGRATED DESEASE MANAGEMENT FOR CHILI FARMING IN BREBES AND MAGELANG - CENTRAL JAVA: SOCIAL ECONOMIC IMPACTS - Joko Mariyono (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2016)
This study aims to analyze the impact of an integrated disease management (IDM) on chilli. Chili disease control technologies that include crop barrier with corn and Crotalaria, and compost tea have been introduced to farmers in Magelang and Brebes. A qualitative approach was used to assess and estimate the socio-economic impact of agricultural research. The study was conducted in 2011. The results showed that based on land use chili, the net economic benefits generated was relatively low. There were only a few farmers who have adopted the technology on chili peppers. Furthermore, the survey also illustrates that three years after its introduction in 2007 the technology status at farm level was just at consciousness phase. Learning of this fact, a thorough evaluation of the technology on chili pepper should be done immediately. Research institutions which have developed the technology should encourage bottom-up initiatives and build a shared commitment to complete the implementation of a clear strategic plan. The adoption of the strategic plan should include the integration of research activities with promotional activities for example by revitalizing participatory approaches to awareness of farmers.